Case report: Patients with positive HER-2 amplification locally advanced gastroesophageal junction cancer achieved pathologic complete response with the addition of pembrolizumab to chemotherapy plus trastuzumab as neoadjuvant therapy - Li, Huanhuan; Ren, Chao; Cui, Donghai; Wu, Tao; Nie, Zhiyong (Frontiers in Immunology, 2025)
BackgroundHuman epidermal growth factor receptor 2(HER-2) is the most prominent therapeutic target for gastric (G)/gastroesophageal junction (GEJ) cancer. Guidelines recommend its use for treating G/GEJ cancers. However, targeted therapy did not significantly improve survival outcomes compared to those with neoadjuvant therapy. The KEYNOTE-811 trial revealed an improved objective response rate (74% vs. 52%; P=.0001) and median duration of response (10.6 vs 9.5 months) with the addition of pembrolizumab (PD-1) to chemotherapy plus trastuzumab compared to that with the addition of placebo in patients with HER-2 overexpression-positive advanced adenocarcinoma. Therefore, addition of PD-1 to chemotherapy plus trastuzumab may lead to a better response in patients with G/GEJ cancer.Case presentationA 66-year-old man was diagnosed with stage III GEJ adenocarcinoma with celiac lymph node metastasis. Immunohistochemical results indicated HER-2(3+) and PD-L1 CPS=5. The patient received three cycles of pembrolizumab plus trastuzumab and chemotherapy preoperatively and underwent radical surgery on November 22, 2022.ConclusionPatients with HER-2-positive locally advanced GEJ cancers received PD-1 immunotherapy combined with trastuzumab and neoadjuvant chemotherapy and achieved a complete pathological response. Hence, it is a novel, highly specific, and potent therapeutic option for HER-2-positive patients and should henceforth be considered as a new treatment approach.